Biophysical Characteristics of Human Follicular Fluid Prior To and After Low Temperature Preservation - Todrin, A. F.; Chub, N. N.; Lipina, O. V.; Chekanova, V. V.; Nipot, E. E.; Pinyaev, V. I.; Todorov, P.; Gorobchenko, O. A. (Problems of Cryobiology and Cryomedicine, 2008)
In the work the basic biophysical parameters of human follicular fluid prior to and after cryopreservation have been investigated. It has been shown an insignificant effect of cryopreservation on osmotic pressure, pH and density of follicular fluid, and a dynamic viscosity of cryopreserved follicular fluid increases approximately by 40%.